Financial Performance and Share Price: Evidence from Manufacturing Firms Before and During the Covid-19 Pandemic - Rohana, Kartika (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The study aims to analyze the effect of financial performance on stock prices. Financial performance is described through five financial ratios as independent variables, namely current ratio, debt equity ratio, return on assets, return on equity and asset turnover, with stock price as the dependent variable. 436 manufacturing companies listed on the Indonesia Stock Exchange (IDX) were used as a sample, which is the 2019-2020 research year (the period before and during the pandemic). Data analysis using multiple linear regression. The results showed the current ratio and return on assets have an effect on stock prices. In addition, in separate tests based on periods, only current ratio had a negative effect on the pre-pandemic period, and return on assets had a positive effect during the pandemic on stock prices. These findings contribute empirically by adding to the literature regarding financial ratios that affect stock prices before and during a pandemic.